Direct and simultaneous determination of As, Cu, and Pb in Brazilian sugar cane spirits by graphite furnace AAS using tungsten permanent modifier with co-injection of Pd/Mg(N03)2 - Caldas, Naíse M. [UNESP]; Filho, Volnei R. Amorim [UNESP]; Gomes Neto, José Anchieta [UNESP] (My University, 2007)
A method was developed using the multi-element graphite furnace atomic absorption spectrometry technique for the direct and simultaneous determination of As, Cu, and Pb in Brazilian sugar cane spirit (cachaça) samples. Also employed was the end-capped transversely heated graphite atomizer (THGA) with platforms pre-treated with W permanent modifier and co-injection of Pd/Mg(N03)2. Pyrolysis and atomization temperature curves were established in a cachaça medium (1+1; v/v) containing 0.2% (v/v) HN03 and spiked with 20 μg L-1 As and Pb and 200 μg L-1Cu. The effect of the concentration of major elements usually present in cachaça matrices (Ca, Mg, Na, and K) and ethanol on the absorbance of As, Cu, and Pb was investigated. Analytical working solutions of As, Cu, and Pb were prepared in 10% (v/v) ethanol plus 5.0 mg L-1 Ca, Mg, Na, and K. Acidified to 0.2% (v/v) HNO3, these solutions were suitable to build calibration curves by matrix matching. The proposed method was applied to the simultaneous determination of As, Cu, and Pb in commercial sugar cane spirits. The characteristic mass for the simultaneous determination was 16 pg As, 119 pg Cu, and 28 pg Pb. The pretreated tube lifetime was about 450 firings. The limit of detection (LOD) was 0.6 μg L-1As, 9.2 μg L-1 Cu, and 0.3 μg L-1Pb. The found concentrations varied from 0.81 to 4.28 μg L-1As, 0.28 to 382 mg L-1 Cu and 0.82 to 518 μg L-1 Pb. The recoveries of the spiked samples varied from 94-112% (As), 97-111% (Cu), and 95-101% (Pb). The relative standard deviation (n=12) was 6.9%, 7.4%, and 7.7% for As, Cu, and Pb, respectively, present in a sample at 0.87 μgL-1, 0.81 mgL-1, and 38.9 μgL-1concentrations.